Pushing the Rehabilitation Boundaries: Hand Motor Impairment Can Be Reduced in Chronic Stroke. (August 2020) - Mawase, Firas; Cherry-Allen, Kendra; Xu, Jing; Anaya, Manuel; Uehara, Shintaro; Celnik, Pablo
Background . Stroke is one of the most common causes of physical disability worldwide. The majority of survivors experience impairment of movement, often with lasting deficits affecting hand dexterity. To date, conventional rehabilitation primarily focuses on training compensatory maneuvers emphasizing goal completion rather than targeting reduction of motor impairment. Objective . We aim to determine whether finger dexterity impairment can be reduced in chronic stroke when training on a task focused on moving fingers against abnormal synergies without allowing for compensatory maneuvers. Methods . We recruited 18 chronic stroke patients with significant hand motor impairment. First, participants underwent baseline assessments of hand function, impairment, and finger individuation. Then, participants trained for 5 consecutive days, 3 to 4 h/d, on a multifinger piano-chord-like task that cannot be performed by compensatory actions of other body parts (e.g., arm). Participants had to learn to simultaneously coordinate and synchronize multiple fingers to break unwanted flexor synergies. To test generalization, we assessed performance in trained and nontrained chords and clinical measures in both the paretic and the nonparetic hands. To evaluate retention, we repeated the assessments 1 day, 1 week, and 6 months post-training. Results . Our results showed that finger impairment assessed by the individuation task was reduced after training. The reduction of impairment was accompanied by improvements in clinical hand function, including precision pinch. Notably, the effects were maintained for 6 months following training. Conclusion . Our findings provide preliminary evidence that chronic stroke patient can reduce hand impairment when training against abnormal flexor synergies, a change that was associated with meaningful clinical benefits.